AlignStatPlot: An R package and online tool for robust sequence alignment statistics and innovative visualization of big data - Alsamman, Alsamman M.; El Allali, Achraf; Mokhtar, Morad M.; Al-Shamaa, Khaled; Nassar, Ahmed E.; Mousa, Khaled H.; Kehel, Zakaria (Public Library of Science, 2024)
Multiple sequence alignment (MSA) is essential for understanding genetic variations con trolling phenotypic traits in all living organisms. The post-analysis of MSA results is a difficult step for researchers who do not have programming skills. Especially those working with large scale data and looking for potential variations or variable sample groups. Generating bi-allelic data and the comparison of wild and alternative gene forms are important steps in population genetics. Customising MSA visualisation for a single page view is difficult, mak ing viewing potential indels and variations challenging. There are currently no bioinformatics tools that permit post-MSA analysis, in which data on gene and single nucleotide scales could be combined with gene annotations and used for cluster analysis. We introduce “AlignStatPlot,” a new R package and online tool that is well-documented and easy-to use for MSA and post-MSA analysis. This tool performs both traditional and cutting-edge analy ses on sequencing data and generates new visualisation methods for MSA results. When compared to currently available tools, AlignStatPlot provides a robust ability to handle and visualise diversity data, while the online version will save time and encourage researchers to focus on explaining their findings. It is a simple tool that can be used in conjunction with population genetics software.